Birth order matters: the effect of family size and birth order on educational attainment - Alison L. Booth; Hiau Joo Kee (Institute for the Study of Labor (IZA), 2005)
We use unique retrospective family background data from the 2003 British Household Panel Survey to explore the degree to which family size and birth order affect a child's subsequent educational attainment. Theory suggests a trade off between child quantity and 'quality'. Family size might adversely affect the production of child quality within a family. A number of arguments also suggest that siblings are unlikely to receive equal shares of the resources devoted by parents to their children's education. We construct a composite birth order index that effectively purges family size from birth order and use this to test if siblings are assigned equal shares in the family's educational resources. We find that they are not, and that the shares are decreasing with birth order. Controlling for parental family income, parental age at birth and family level attributes, we find that children from larger families have lower levels of education and that there is in addition a separate negative birth order effect. In contrast to Black, Devereux and Kelvanes (2005), the family size effect does not vanish once we control for birth order. Our findings are robust to a number of specification checks.
Keywords: I2; J1; 330; family size; birth order; education; Familiensoziologie; Familie; Kinder; Bildungsverhalten; Bildungsniveau; Schätzung; Großbritannien